2005
DOI: 10.5424/sjar/2005032-142
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of seed physical traits in upland cotton under different temperature regimes

Abstract: Physical seed traits such as seed weight, volume and density are determinants of seed vigour in cotton, while seed surface area is of prime importance in lint production. Two Pak-upland cotton crosses, plus their parental, F 2 and back cross generations were evaluated over two years to determine the inheritance pattern of their seed physical traits under heat stress and non-stress field regimes. The heat stress regime suppressed the average expression of seed traits in all generations. The results showed there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This supports the findings of earlier studies by Drabo et al (1984), Lopes et al (2003) and Noubissié et al (2007). As reported by Lopes et al (2003), Konak et al (2007) seed physical properties are genetically controlled but the implementation of the program is affected by the environmental factors in particular moisture content and temperature (Rahman et al, 2005;Yalcin, 2007). Baryeh (2001) evaluated physical properties of Vigna subterranea seed as function of grain moisture content varying from 5% to 35% (wb) and observed in this moisture range, the 100 seed mass increased from 50.02g to 80.06g, the grain surface area increased from 304 to 495 cm 2 , the sphericity decreased from 0.90 to 0.82 while the porosity increased non-linearly from 38.0 to 43.8% between 5% to 20% grain moisture and then decreased to 40.5% at 35%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This supports the findings of earlier studies by Drabo et al (1984), Lopes et al (2003) and Noubissié et al (2007). As reported by Lopes et al (2003), Konak et al (2007) seed physical properties are genetically controlled but the implementation of the program is affected by the environmental factors in particular moisture content and temperature (Rahman et al, 2005;Yalcin, 2007). Baryeh (2001) evaluated physical properties of Vigna subterranea seed as function of grain moisture content varying from 5% to 35% (wb) and observed in this moisture range, the 100 seed mass increased from 50.02g to 80.06g, the grain surface area increased from 304 to 495 cm 2 , the sphericity decreased from 0.90 to 0.82 while the porosity increased non-linearly from 38.0 to 43.8% between 5% to 20% grain moisture and then decreased to 40.5% at 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends were reported by Lopez et al (2003) and Hossain et al (2010) who noted that the type of allelic interaction predominant between the genes that condition variability in cowpea seed weight is additive. Gupta et al (1984), Rahman and Saad (2000), Rahman et al (2005) also found positive and significant additive genetic effects for seed weight of Pisum sativum, Vigna sesquipedalis and Gossypium hirsutum respectively. This result is crucial for breeding programs because additive variance, which depends only on the contribution from homozygotes and can be fixed by selection, is the most important component in gain prediction expressions.…”
mentioning
confidence: 95%
See 3 more Smart Citations